Opinie nauczycieli przedszkoli integracyjnych na temat szans powodzenia działań włączających wobec poszczególnych grup uczniów, a staż pracy w zawodzie - Chrzanowska, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Currently, the idea of inclusive education is perceived as a model of education, far exceeding the idea of inclusion of students with disabilities into mainstream education. It is a vision of a school aimed at considering the needs of all students, i.e. those who exhibit no severe developmental disabilities, with special educational needs, including gifted individuals. Additionally, the scholars of inclusive education agree, that the process is neither easy nor simple. One of the determining factors indicated, is the attitude of teachers towards the very idea. Therefore, a research idea arose, aiming at examining the opinion of teachers regarding the subject of inclusive education, as a potentially dominant form of education. Recognising at least some of its determinants seemed essential. The following article focuses on two of the aforementioned: types of institutions, where the teachers are employed, and the teachers’ professional experience. The research encompasses integrated preschools. It seems that the experience of teachers of such institutions proves particularly significant for recognising the chances and dangers of inclusive education, within the context of Polish integration experience. The two professional groups distinguished, with substantial and minor professional experience, allow to examine the perspective of inclusive action.